A structure equation model of indicators driving BIM adoption in the Bahraini construction industry. Issue 1 (28th October 2019) - Ahmed, Shurooq H.A.; Suliman, Saad M.A.
Abstract : Purpose: This study aims to establish an adoption model using Structural Equation Modeling (SEM) that examines the relationship between several key indicators that drive building information modeling (BIM) adoption. Design/methodology/approach: The study was carried out using quantitative approaches through the Delphi method and questionnaire survey. A total of 272 completed responses were collected and analyzed through the SEM technique using SPSS 25 and AMOS software. Findings: The structural model shows that "environment" and partially "people" indicators are the leading indicators driving BIM adoption with path coefficient values of 0.280 and 0.332, respectively. Originality/value: It is expected that these conclusions will lead the Bahraini construction industry stakeholders to raise the level of BIM adoption.